Same but different? A qualitative analysis of the influence of COVID-19 on law enforcement and organized crime in Germany - Schreier, Sarah (Trends in organized crime, 2023)
Criminological research on COVID-19 and its repercussions on crimes, criminals and law enforcement agencies is still in its infancy. This paper fills that void with regard to the influence of COVID-19 on organized crime and the work of law enforcement agencies’ investigations of organized crime in Germany by presenting empirical findings from a nationwide qualitative interview study. Through the methodological combination of Grounded Theory and Situational Analysis, we find three central narratives (us vs. them, nationalization vs. internationalization, conservatism vs. innovation) that were provided by law enforcement personnel in terms of the way in which COVID-19 influenced both organized crime groups and their work in the investigation thereof. Following a reflexive approach, the implications of COVID-19 on the research process itself are also discussed.